Pengaruh Social Media Engagement, Digital Trust, dan Kualitas Informasi terhadap Citra Organisasi Publik di Era Transformasi Digital (Studi pada Mahasiswa S-1 sebagai Digital Native) - Bayu Suratmoko Bayu; Mohammad Rafii; Ahyar Junaedi; Jaemi Wahyudi; Saipul (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2026)
The way public organizations operate has been profoundly altered by digital transformation communicate with the general population, especially by using social media is the principal channel of communication. In the impression, information quality, digital trust, and social media participation are significant elements that could affect how public institutions are perceived. This study aims to investigate how learners that are digital natives perceive public organizations in relation to social media engagement, digital trust, and information quality. Purposive sampling procedures were used to choose 250 undergraduate students from Muhammadiyah University Palangka Raya as respondents for this quantitative study with an explanatory design. A Likert scale-based the data was collected via a questionnaire, and it was analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) utilizing SmartPLS software. According to the results, every construct satisfied the authenticity and dependability requirements. The model's structural evaluation revealed that 58.8% of the variation in Public Organization Image was simultaneously explained by Information Quality, Digital Trust, and Social Media Participation. After information quality along with social networking engagement, digital confidence has the greatest positive and substantial impact on public organization image, according to hypothesis testing. Furthermore, the predictive relevance value demonstrates the model's strong forecasting powers. These results demonstrate that, In the era of the digital shift, the main elements influencing how public institutions are seen are digital trust and information quality. This study offers practical implications for public organizations in developing successful digital communication strategies to improve organizational image and public trust, in addition to theoretical contributions to the body of literature on public organization digital communication.